Computerization of libraries of educational institutions in Mindanao - Pellazar, Veronica C. (1996)
This study was conducted to find out the status of the computerization of libraries of educational institutions in Mindanao. The chief librarians of each of the 243 libraries of educational institutions in Mindanao as of 1995 were the respondents of the study. The descriptive method was used with questionnaire as a data-gathering tool.